PREDICTORS OF HYPOXEMIA IN BRONCHIOLITIS IN A SAMPLE OF IRAQI INFANTS - Nafie Hameed, Numan; AL-Janabi, Muhi K.; Omar Hamad, Cawes (Journal of the Faculty of Medicine Baghdad, 2008)
Background: Bronchiolitis is the first episode of wheezing associated with low grade fever, rhinitis, tachypnea, and increasing respiratory effort in a previously healthy infant during the winter months, and it is the most common lower respiratory tract infection in infancy. Objectives: This study is designed to analyze the clinical signs and symptoms alone or as combinations as possible predictors of severe hypoxemia in infants with bronchiolitis. Patients and methods: This is a prospective study, which was carried out on 96 infants with a mean age of 7.74 ±3.72 months who were admitted to Children Welfare Teaching Hospital in Medical City-Baghdad with bronchiolitis during the period from 1st October 2006 to the 15th March 2007. They are divided into two groups: group one 46 cases (oxygen saturation (SaO2<90) and group two, 50 cases (SaO2≥90).Complete history taken from care taker and full examination done for each patient. A portable oximeter was used to measure oxygen saturation. Results: Forty nine (51%) of patients were males and 47 were females (49%), with male to female ratio of 1.04:1. The mean age was (7.745±3.7) months. The mean oxygen saturation was (90%), with a median of (84.7%) and a range of (76%-89%) in group one (SaO2<90), while it was (95.32%) with a range of (90%-99%) in group two (SaO2≥90). Conclusions: Reduced ability to feed, sleep disturbances, hypotonia and clinical signs as suprasternal retractions, continuous nasal flaring, tachypnea, grunting, head nodding and cyanosis appeared to be statistically highly significant in this study as predictors of severe hypoxemia. Combinations of signs and symptoms that showed statistically significant association with severe hypoxemia were: grunting or head nodding, cyanosis or head nodding, tachypnea or sleep disturbance, tachypnea or suprasternal retractions, and tachypnea or head nodding (p.value <0.0001) for all mentioned combinations, So we recommend to use these combinations of signs and symptoms as significant predictors of severe hypoxemia especially when pulse oximetry is not available.